Chronic Intestinal Pseudo-Obstruction - ABM Moniruddin; Md Rashed Khan; Baikaly Ferdous; Tanvirul Hasan; Hamida Begum; Sofiuddin Mohammad Obayed; Romana Rafique; M A Rouf; Md Masudar Rahman; Sayeed Bin Sharif (KYAMC Journal, 2025)
CIPO (Chronic Intestinal Pseudo-Obstruction) is an uncommon heterogeneous clinical syndrome of variable severity, featured by disordered GI (gastrointestinal) motility, and its presentations simulate those of recurrent partial or complete intestinal obstruction in the form of radiologically dilated small or large intestine with air-fluid levels in the absence of any identifiable mechanical cause. It results from a complex disordered interaction amongst the altered gut flora/microbiota, the enteric smooth musculature (myopathies), the enteric nervous system (neuropathies), the intestinal endocrine system (endocrinopathies) and mesenchymopathies, etc. It poses a definite challenge to the treating physicians, despite some improvement in diagnostic and therapeutic strategies. Because of non-specific symptoms and clinician’s lack of discretion, there is every possibility of misdiagnosis. Commonly imaging, manometry and sometimes histopathological examination of biopsy specimens are undertaken as diagnostic tools. With surgical advancements, small gut transplantation is an expected treatment option for advanced CIPO. In general, the CIPO patients have increasingly worsening chronic symptoms, with poor prognosis, warranting nutritional and surgical interventions. This review article explains the features of CIPO and the latest avantgarde management strategies, with a view to upgrading clinicians' knowledge about CIPO, categorically summarizing the diagnostic tools and other issues to enlighten the clinicians, resulting in easy, quick, accurate and exact diagnosis of this clinical syndrome for proper and adequate treatment without delay, improving the patients’ quality of life, minimizing sufferings. This review, in addition further focuses to the significance of continued research for more elaborately searching the etiology and the more effective management strategies of CIPO patients. KYAMC Journal. 2024; 15(02): 94-104